Functions of phenyl sulfide in polyimide as the electrode coating film to suppress the metal-particle motion within DC GIL. (June 2020) - Huang, Xuwei; Wang, Jingrui; Wang, Jian; Li, Qingmin
Graphical abstract: Highlights: Direct coating of S-contained PI on the electrodes doubles the DC lifting voltage of free metal particles compared with uncoated electrodes. S-contained PIs are prone to bond with metal, leading to a preferable-adhesive electrode coating, as elaborated by ReaxFF MD simulations. A theoretical model is proposed to describe metal particle motion dynamics, by which the suppression effect of PI coating is characterized. Abstract: Polyimides containing diphenyl sulfide units were directly coated on the Aluminum electrodes via solution polycondensation-thermal imidization method, which is important for suppression of the free metal particle motion in the Direct Current Gas Insulation Transmission Line (DC GIL). The micro-structures were identified by Fourier-transform infrared spectroscopy (FT-IR). A self-designed experimental platform with plate-to-plate electrode configuration was constructed, by which the metal particle motion behaviors were traced and studied under high voltage DC stresses. To clarify the functionality of phenyl sulfide in the polyimide, the physicochemical properties including thermal and dielectric properties as well as adhesion works were tested accordingly. The microscopic interactive scenarios between polyimides and the electrodes were elucidated by reactive force field molecular dynamics (ReaxFF MD) simulations. The experimental and simulated results were correlated, and also compared with that from the non-sulfur contained polyimide specimen. For the spherical Aluminum particles, a significantly improved DC lifting voltage up to 21.12 kV was achieved by the sulfur-contained polyimide coating, due to the fact that sulfur in the polyimides will increase the dielectric constant as well as the adhesion strength with metal particles. Also, the changes in bulk conductivity are correlated more closely to the variation of particle-motion behaviors after being lifted in the DC electric field. The observed results show that, the inclusion of sulfur element can effectively enhance the adhesion between the polyimide film and the DC GIL Aluminum electrode, as sulfur in the diamine structure of polyimide is more likely to bind with Aluminum than oxygen.